ANALISIS PERBANDINGAN PERSENTASE REJECT SEBELUM DAN SETELAH PENERAPAN PROJECT IMPROVEMENT TEAM DI MESIN CUPFORMING LINE 3 DI PT D dan D PACKAGING INDONESIA - Iin Alma Pegaria (Universitas Mercu Buana, 2013)
Abstract: The thesis aims to solve the problem in reducing reject level using PDCA and8 Steps Quality Improvement. The results shows that the most dominant reject cupbecause leak. Root causes of this reject caused by limitation of training to operator,machine problem, no machine setting guidance and usage of more than one type ofmaterial. Base on the root causes then improvements that have been made are operatortraining, improved the machine, producing guidelines for setting the machine, andallocation of material every single type of material in a period of time.Keywords: PDCA, 8 Steps Quality Improvement, Reject Cup Forming.